Co-creation and the development of SME designer fashion enterprises. Issue 3 (11th July 2016) - Millspaugh, Jennifer; Kent, Anthony
Abstract : Purpose: – The purpose of this paper is to examine the co-creation of small and medium enterprise (SME) designer fashion brands during internationalisation. Design/methodology/approach: – As an exploratory study, this research utilises grounded theory methodology and incorporates the use of 38 semi-structured in-depth interviews with designer fashion enterprises (DFEs) and their support network of sales and PR agencies. Findings: – Co-creation was identified as an important element for the successful integration of the entrepreneurial DFE into the global fashion industry network. Within relationship marketing, the concept of co-creation emphasises consumer experience, influence and power in the development of brand value. However current understanding of co-creation inadequately explains the development of the entrepreneurial designer fashion brand, requiring examination of the concept using grounded theory. The findings of this research highlight how these SMEs react and respond to the interpretation of their brand identity through the co-creation process as they seek to introduce and grow their firms within the global fashion marketplace. Originality/value: – This paper identifies the influence of industry stakeholders on the process of fashion brand co-creation. Additionally, by identifying the process by which the entrepreneurial DFE navigates the introduction of their collections to the industry's network, and responds to interpretations of the firm's brand identity, this paper recognises the influence of the firm throughout the co-creation process.